2014
DOI: 10.4028/www.scientific.net/amr.996.325
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Residual Stress Field Uniformity when Using the Ring-Core Method

Abstract: Abstract. The evaluation of residual stresses using Ring-Core method requires complex analysis of the acquired strain values. The development is based on ASTM Standard E837-08 for hole-drilling method, but the specific approach for Ring-Core is needed. The input data sets obtained from strain gage rosette are categorized by proposed uniformity test. The influence of geometric parameters of the specimen on this test and subsequently on the both uniform and nonuniform calculations is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Non-uniform steps, for example, as initially proposed by Zuccarello, 6 and recently re-proposed by Menda et al 8,9 and Zuccarello et al, 10 can also be obtained from the large matrices introduced above. However, the depths need to be approximated with the 0.1-mm resolution.…”
Section: Integer Multiple-step Coefficient Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-uniform steps, for example, as initially proposed by Zuccarello, 6 and recently re-proposed by Menda et al 8,9 and Zuccarello et al, 10 can also be obtained from the large matrices introduced above. However, the depths need to be approximated with the 0.1-mm resolution.…”
Section: Integer Multiple-step Coefficient Determinationmentioning
confidence: 99%
“…Hole-drilling is a well-established procedure defined by internationally accepted standards. 1,2 Ring-core was introduced more than 20 years ago; [3][4][5][6] however, it was deeply investigated and developed only recently, especially in terms of sensitivity and uncertainty analysis, [7][8][9][10] and even applied at the microscale. 11,12 In hole-drilling, the material is removed at the centre of a rosette, and thus the relaxed strains are measured at the periphery of the hole, whereas in ring-core the strains are measured in the central internal region, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Recently, the ring core method has been explored by researchers. [10][11][12][13] Calibration coefficients for ring core were determined by Menda et al [10][11][12][13] for a model with 14 mm of the ring core notch inner diameter and 18 mm of outer diameter. 10 Authors also have reported the effect of trepan cutter geometry with respect to the slope at the bottom of cutting teeth on the calculation of residual stress.…”
Section: Introductionmentioning
confidence: 99%
“…However the connections between experimental measurement and simulation studies is still not sufficient which is showed by lack of some international standard. Prerequisite for experimental usage of the Ring-Core method for evaluation of the residual stress components in material is the determination of adequate calculation coefficients and constants [1,2,3]. Sensing of the stress changes inside the material by the sensor attached at the top of the component is not suitable by using the classic Hook´s law.…”
Section: Introductionmentioning
confidence: 99%